Vertebral spine of Tamandu-mirim Tamandua tetradactyla - Sesoko, Natalia Ferreira [UNESP]; Bortolini, Zara [UNESP]; Merlini, Natalie Bertelis [UNESP]; Evangelista, Felipe Carvalho [UNESP]; Rahal, Sheila Canevese [UNESP]; Machado, Vania Maria de Vasconcelos [UNESP]; Teixeira, Carlos Roberto [UNESP] (Univ Federal Rural Pernambuco, 2011)
Anatomical studies of the anteater (Tamandua tetradactyla) are scarce and the articles that describe the vertebral column of this species have variations in the number of thoracic and lumbar vertebrae. This study had the objective of adding data to the existing literature about the anatomical composition of an anteater's vertebral column using radiographic and tomographic exams. Based on the cadaver of a young female anteater, we observed a total of 7 cervical, 16 thoracic, 3 lumbar and 5 sacral vertebrae, which differed from the cited literature, especially with respect to the thoracic vertebrae. This demonstrates the need for studies with a larger number of individuals in order to standardize possible anatomic variations for the species.
Keywords: vertebrae; anatomy; imaging; anteater